2022
DOI: 10.1016/j.cmi.2021.09.035
|View full text |Cite
|
Sign up to set email alerts
|

A new SARS-CoV-2 variant with high lethality poorly detected by RT-PCR on nasopharyngeal samples: an observational study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A single variant lineage, B.1.616, does contain E:T30I as a lineage-defining mutation. Interestingly, B.1.616 was associated with an extremely localised, largely nosocomial-associated outbreak, suggesting the possibility this may have been the emergence of a virus from a long-term infection ( Fillâtre et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A single variant lineage, B.1.616, does contain E:T30I as a lineage-defining mutation. Interestingly, B.1.616 was associated with an extremely localised, largely nosocomial-associated outbreak, suggesting the possibility this may have been the emergence of a virus from a long-term infection ( Fillâtre et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A single variant lineage, B.1.616, does contain E:T30I as a lineage-defining mutation. Interestingly, B.1.616 was associated with an extremely localised, largely nosocomial-associated outbreak, suggesting the possibility this may have been the emergence of a virus from a long-term infection (Fillâtre et al, 2021). This also raises the hypothetical possibility that E:T30I may be considered a marker of long-term SARS-CoV-2 infections.…”
Section: E-gene Recurrent Mutationsmentioning
confidence: 99%
“…In a number of the included articles a combination of exposure ascertainment approaches was adopted. One included article reported an additional exposure ascertainment approach, namely, Fillâtre et al [114] classified high-risk contacts of a COVID-19 case based on the identified variant of infection of this case. Furthermore, we presented potential selection biases (e.g., overcontrol bias, endogenous selection bias, sample truncation bias).…”
Section: Discussionmentioning
confidence: 99%